Effect of six weeks of high intensity interval training on under-Carboxylated Osteocalcin serum levels, insulin resistance, and lipid profile in overweight girls: randomized clinical trial - Fatemeh Fakhri; Somaye Fakhri; Saeed Shakeryan; Aliakbar Alizadeh (Mashhad University of Medical Sciences, 2021)
Introduction: Physical activity and exercise through different mechanisms can promote health in individuals.The body's bone tissue can alter glucose and fat metabolism under the influence of physical activity and exercise. Therefore, this study was performed with aim to investigate the effect of high intensity interval training (HIIT) on serum levels of under-carboxylated osteocalcin, insulin resistance and lipid profile in overweight girls. Methods: This randomized controlled clinical trial study was performed on 24 overweight female students (body mass index: 28.58±2.38) in Shahid Chamran University of Ahvaz in 2020. The subjects were randomly divided into two groups of 12-member: HIIT and control. The training group practiced for 6 weeks (3 sessions per week), while the control group did not have any regular physical activity. Blood samples were obtained for measurement of serum level of Osteocalcin, glucose, insulin and lipid profile (48 hours before and after the intervention period). Data were analyzed by SPSS software (version 23) and paired-t and independent t-test. P<0.05 was considered statistically significant. Results: Performing high intensity interval training for 6 weeks led to an increase in serum levels of under-carboxylated osteocalcin (P=0.045), significant decrease in glucose (P=0.026), insulin resistance (P=0.036), triglycerides (P=0.017) and LDL (P=0.04) in overweight girls; while, no significant changes were observed in other components of lipid profile (total cholesterol and HDL) (P≥0.05). Conclusion: Performing high intensity interval training led to a significant improvement in insulin resistance and some features of the lipid profile (triglycerides and LDL). This may be due to an increase in the endocrine function of the bone (under-carboxylated osteocellin).